Is aerobic endurance a determinant of cardiac autonomic regulation? - Bosquet, L; Gamelin, F. X.; Berthoin, S. (European Journal of Applied Physiology, 2007)
The aim of this study was to determine if subjects matched for [(V)\dot]O2 maxVO2max but with differing aerobic endurance displayed similar heart rate variability (HRV) at rest and heart rate recovery (HRR) after maximal exercise. We hypothesized that the higher the aerobic endurance, the higher the HRV and the faster the HRR. Twenty-eight well trained middle- and long-distance runners (24 men and 4 women) performed a maximal continuous graded exercise test for the determination of maximal oxygen consumption ([(V)\dot]O2 max),(VO2max) ventilatory threshold (VT), peak treadmill velocity (PTV) and HRR, as well as a test to measure the autonomic regulation of heart rate during supine rest, using HRV analysis. Once both tests were completed, subjects were matched for [(V)\dot]O2 maxVO2max and assigned to the low endurance or the high endurance group, depending on the %PTV at which VT occurred (81.9 ± 2.9 and 88.3 ± 3.1%PTV for both groups, respectively; P < 0.0001). Contrary to our hypotheses, neither HRV nor HRR parameters were different between groups or associated with aerobic endurance. [(V)\dot]O2 maxVO2max (59.0±7.3 ml min-1 kg-1) was inversely correlated with ln SDNN (r = -0.44, P < 0.05), ln HF (r = -0.52, P < 0.05), ln LF + HF (r = -0.53, P < 0.05). These results suggest that aerobic endurance is not associated with cardiovascular autonomic control, as measured by HRV and HRR.